PENDIDIKAN ISLAM MENGHADAPI REVOLUSI INDUSTRI 4.0 - Yayat Suharyat; Agustina Agustina; Muzayyanah Yuliasih (Fakultas Agama Islam Universitas Ibn Khaldun Bogor, 2018)
This research is motivated by the condition of Islamic Education as an important subject in the formation of noble values of students. Islam as a religion which is a system of belief and belief greatly influences actualization in the context of education. Formulation of the proposed problem is: